Mercado imobiliário informal e dinâmica urbana: o caso do bairro de Mãe Luiza Natal/RN - Amaral, Carmem Cristina Fernandes do (2011)
This paper aims at analyzing the dynamics of informal housing in Mãe Luiza, in the context of real estate valuation of the city of Natal/RN, which, like any other urban center, has problems related to access to urban land, which increasingly more is appreciated due to their scarcity and, consequently, has led to the segregation of urban spaces. Recently, the informal housing market has received special attention by scholars who wish to discuss the production of space and ways of access to urban land and housing, especially for those disadvantaged by the housing policies of the government where these exist. When talking about the housing market, we are automatically referring to concepts or categories intrinsic to the existing mode of production in our society - the capitalism. Thus, the categories: income, value (use and exchange), commodity, capital, profits and capital gains, along with other important concepts as well as land use (urban) and real estate agents are of great relevance to discussion we intend to do within the context of production space